The Impact of Internet Finance on Commercial Banks Efficiency in China - Pang, Meng (2018)
This dissertation uses two-step Stochastic Frontier Analysis to estimate the impact of the development of internet finance on commercial bank (State-owned commercial banks, Joint-stock commercial banks, and City commercial banks) efficiency in China. The dataset involves 452 bank-year observations during the period of 2011-2017. The development of internet finance is related to the development of Third Mobile Payment and Third Internet Payment. The results suggest that the change in annual average overall cost efficiency is greatly influenced by City commercial banks, and the bank inefficiency is negative related to the GDP growth, bank profitability, equity structure, risk management ability, bank scale, and the development of internet finance.